A significant antihypertensive effect of Holarrhena floribunda supported by an exploratory phytochemical study - Kafui Kpegba; Etonam Tété Kondo; Oudjaniyobi Simalou; Komlatsè Togbenou; Pakoupati Boyode; Outéndé Toundou; Nagba Yendoubé Gbandjaba; Amegnona Agbonon; Messanvi Gbeassor (Shahrekord University of Medical Sciences, 2018)
Introduction: Holarrhena floribunda (G.Don) T.Durand & Schinz is a tree that can grow up to 25 m with white latex in its organs. The bark of this plant is commonly used in traditional medicine to treat dysentery, diarrhea, diabetes, malaria, and high blood pressure. In this study, phytochemical groups were widely investigated on trunk bark as well as on leaves of H. floribunda harvested in Danyi (Togo). Antioxidant activity and antihypertensive properties of the plant extracts were also evaluated on sound guinea pigs. Methods: The hydro-ethanolic extract of the trunk bark was prepared and antioxidant activity was evaluated via the DPPH radical-scavenging and the ferric-reducing antioxidant power (FRAP) methods, and via the determination of the total phenolics content. This hydro-ethanolic extract was used to assess the plant extract effect on blood pressure of sound guinea pigs. Results: So, phytochemical screening revealed that H. floribunda contained most of the phytochemical groups. The 50% inhibitive concentration of that extract by DPPH was 29.80 ± 0.001 μg/mL. The equivalent of Fe2+ by FRAP was 1009.9 ± 0.6 μmol/g of dry extract. The content of phenolic compounds was 139 ± 0.053 mg GAE (gallic acid equivalents)/g of dry extract. Intravenous injection of the extract (10, 20, 40, 80 mg/kg) via the invasive method in guinea pigs under normal strain caused a decrease in diastolic blood pressure, systolic blood pressure, and so in mean arterial pressure (MAP) by dose cumulative and time-dependent. Conclusion: The results show that hydro-ethanolic extract of H. floribunda trunk bark has antihypertensive and antioxidant properties. This might be the reason for the use of that extract for the treatment of hypertension in traditional medicine.